Depicting past stress history at passive margins: A combination of calcite twinning and stylolite roughness paleopiezometry in supra-salt Sendji deep carbonates, Lower Congo Basin, west Africa. (June 2023) - Zeboudj, Aniès; Bah, Boubacar; Lacombe, Olivier; Beaudoin, Nicolas E.; Gout, Claude; Godeau, Nicolas; Girard, Jean-Pierre; Deschamps, Pierre
Abstract: The paleostress history and associated deformation mechanisms affecting passive margins are seldom studied, as access to offshore parts is rather limited. We analyze an offshore wellbore core of the Albian, post-rift carbonates of the Sendji Fm which directly overlies the salt of the Aptian Loeme Fm in the Lower Congo Basin. Paleopiezometry based on stylolite roughness inversion (SRIT) and calcite twin inversion (CSIT) was combined with fracture analysis, U–Pb geochronology of calcite cement and burial modeling to unravel the orientations and magnitudes of horizontal and vertical stresses affecting the Sendji Fm over time, with a focus on the impact of salt tectonics on stress records. The results of SRIT on bedding-parallel stylolites constrain the range of depths over which the Sendji Fm strata deformed under a vertical principal stress σ1 to 650–2800 m (median ∼1300 m). Once projected onto the burial model derived from TemisFlow™ software, the range of depths converts to a period of pressure solution activity, from 101 to 15 Ma. Calcite twin measurements within the early diagenetic cement (U–Pb age = 101 ± 1 Ma) reveal three main types of stress regimes: (1) extensional stress regimes with σ3 trending ∼ N–S and ∼E-W associated with local, thin-skinned salt tectonics (101–80 Ma), (2) strike-slip stress regimes with σ1 trending ∼ NW-SE to NNE-SSW and a compressional stress regime with σ1 trending NNW-SSE, reflecting possible intraplate stress transfer from the distant Africa-Eurasia plate boundary (67–60 Ma); (3) a strike-slip and a compressional stress regime with σ1 trending E-W likely related to the mid-Atlantic ridge push possibly combined with effects of variations in elevation and density of the lithosphere and sedimentary flexural loading (15 Ma to present). The paleostress sequence suggests that the sedimentary cover was decoupled from the crust during salt tectonics and then recoupled from the late Cretaceous onwards. Highlights: The paleostresses affecting deep carbonates are characterized by studying an offshore core in the west African passive margin. The timing of the successive stress regimes in the Sendji Fm is constrained. Local gravitational stress from salt tectonics and far-field tectonic stress from plate boundaries influenced the margin. The potential of a multi-proxy approach is established.